'They call me headmaster': Malawian and Australian women leaders. Issue 2 (17th February 2018) - Whitehead, Kay; Andretzke, Elaine; Binali, Valesi
ABSTRACT: This article explores commonalities in the lives and work of women head teachers in Malawian secondary schools and women principals in Australian Lutheran schools. In both Australia and Malawi women are under-represented in school leadership and often appointed to complex schools and communities. We commence with a brief discussion of Malawi and Australia's political and educational histories which have much in common, before outlining current selection policies for school leadership. The second part of the article explores women leaders' initial and ongoing challenges in relation to their school systems, daily work and domestic lives. The final section focuses on their perspectives of current strategies to address women's under-representation as leaders in their respective school systems. Notwithstanding the stark contrast in socio-economic contexts, we highlight enduring transnational inequalities in women leaders' lives and work in Malawian secondary and Australian Lutheran schools.